Tes Psikologi Online Program Studi Psikologi Universitas Sahid Surakarta - Shomad, Abdush; Cristya, Arkha; Santoso, Joko; susilo, Dahlan (JURNAL GAUNG INFORMATIKA, 2010)
Intellectual intelligence is one of the human intellect, and can be measured against the test tool. The system is a Web-based software that can be shared through the internet network. Test System Intellectual Intelligence (IQ) is Web Based Other forms of intelligence tests, which change the shape of a software test tool that can be accessed via the Internet (online). LPT Solutions is an organization engaged in counseling psychology, which became our partner in the development of this system. The problems that arise are how to design, implement and later mengenbangkan the system. In order to solve the problem of system design metoden John Burch, Gary Grudnitski. Currently the system has been completed diinplementasikan, tested and uploaded with the domain name "http://solusi-psycho.net", which serve registration and online IQ tests.